A methodology for transforming BPMN to IFML into MDA - Abir Sajji; Yassine Rhazali; Youssef Hadi (Bulletin of Electrical Engineering and Informatics, 2022)
Responding to rising information system complexity and the high expense of technological migration, model driven architecture (MDA) was created. As a result, the OMG advocates raising the abstraction level to overcome technological limitations. MDA seeks to describe the functional and performance requirements of an application on a platform independently. Using the MDA approach, the business process model and notation (BPMN), and interaction flow modeling language (IFML) standards, we represent a methodology that allows transforming semi-automatically from the computation independent model (CIM) level to the platform independent model (PIM) level; to achieve this a collection of unique rules for transforming in a semi-automatic manner from CIM to PIM were developed. At the CIM level, we create models of business process using the notation standard BPMN, and IFML is used to adapt PIM models with web-oriented graphical user interfaces (GUI). To properly demonstrate the transformation procedure from CIM to PIM models a case study of the order management process was presented.